1977
DOI: 10.2190/2b2a-f34l-0txg-wnq7
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Published Medical Reference Citations

Abstract: Among 2, 195 reference citations, published during 1975 in ten major US medical journals, 634 (29%) were found to be erroneous on direct checking of the original source. The percentage of error within individual journals ranged from 14 to 50 per cent. Such a high error rate would seem to seriously diminish the usefulness of published reference lists and, possibly, raise questions about the accuracy of other portions of the literature also.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 0 publications
1
12
0
1
Order By: Relevance
“…A simple explanation for this is that authors follow ‘least-effort behaviour’25 or are poor, careless or even flippant in their referencing 24 26. Another could be that authors’ reference management concepts on a surface level were without a deep understanding of the consequences and implications of the concept.…”
Section: Discussionmentioning
confidence: 99%
“…A simple explanation for this is that authors follow ‘least-effort behaviour’25 or are poor, careless or even flippant in their referencing 24 26. Another could be that authors’ reference management concepts on a surface level were without a deep understanding of the consequences and implications of the concept.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the bibliographic accuracy of citations in medical journals. An early study by Goodrich and Roland (1977) found, on direct checking of the original source, that among 2195 reference citations of ten major U.S. medical journals, published during 1975, 634 (29%) were erroneous. Another study that verified citations prior to publication in a single journal over a 13-month period displayed 1005 (54%) incorrect citations and 115 (6%) unverified citations out of 1867 references (Key and Roland, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…In the Goodrich and Roland (1977), Hartmann (1984), Key and Roland (1977), and Poyer (1979) studies, error rates relative to year of publication ranged from 0.4% to 2.0%. The rate for both CES and JCP was 1.9%.…”
Section: Resultsmentioning
confidence: 99%
“…Total errors and faults detected revealed the following counts and percentages: 634 (28.9%) by Goodrich and Roland (1977), 1,005 (57.4%) by Key and Roland (1977), and 466 (19.0%) by Poyer (1979). In one study Boyce and Banning (1979), using two nonmedical journals, reported 66 errors (17.6%) in the Journal of the American Society f o r Information Science for issues appearing in 1976 and 84 errors (13.2%) in the Personnel and Guidance Journal for issues appearing in the same year.…”
Section: Data From Previous Studiesmentioning
confidence: 99%